KUALITAS AIR SUNGAI DI DESA TANIPAH (GAMBUT PANTAI), KALIMANTAN SELATAN - Sanjaya, Rahmat Eko; Iriani, Rilia (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2018)
Tanipah village is a coastal village in Kecamatan Aluh-Aluh, Kabupaten Banjar, Kalimantan Selatan and a tidal area of sea water. Tanipah villagers utilize river water for daily needs, so the quality of river water is a major concern. The results of this research are expected to be informations for the community about quality of river water in Tanipah. This research is a survey research and the analysis was conducted in-situ and ex-situ. The analysis was done by comparing the test result against the predefined quality standard. River water temperature in Tanipah ranges from 280C â 33,60C and has no taste and no smell. Turbidity of 54,8 NTU, indicating river water is not feasible for consumption. Dissolved oxygen is 5,9 mg/L and is in the mild contaminated category. The COD and BOD value respectively 17,03 mg/L and 6,70 mg/L, exceeds the limit of the class I water quality standard. The pH value is at 7,33, indicating that the pH is normal. The iron concentration is 1,71 mg/L, exceeds the maximum permissible level for drinking water quality. Other metals likes Mn, Pb, Cu and Cd, are within thresholds for the waters. River water in Tanipah village based on the value of dissolved oxygen, is in category of light contaminated. Thus, in general, river water in Tanipah village can only be used for class III water, as irrigation.